(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
One impact of the industrial revolution is the development of computer systems, including the birth of ChatGPT. ChatGPT (Generative Pre-trained Transformer) is a large-scale natural language processing model developed by OpenAI to generate text similar to human language. The model is trained on massive textual data and can produce diverse text output, including chatbot responses, article summaries, concept explanations, and more. The ability of ChatGPT influences the way of writing, including scientific writing.